Analysis of Factors Affecting the Growth of MSMEs in the Leading Sector of Capture Fisheries Commodity Processing in Masohi City and Amahai Districts, Central Maluku Regency - Wa Hayumi; Stellamaris Metekohy; Fahrudin Ramly (PT Mattawang Mediatama Solution, 2024)
The purpose of the study was to determine the effect of capital, labor, promotion and sales methods on the turnover of MSMEs in the leading sector of capture fisheries commodity processing in Masohi and Amahai Districts, Central Maluku Regency. For this purpose, a sample of 32 MSME actors was taken as respondents. The collected data were analyzed using multiple linear regression. The results showed that capital and labor had a positive and significant effect on MSME sales turnover, while promotion had a positive but not significant effect while the sales method had a negative and insignificant effect. .